2010
DOI: 10.1002/acr.20036
|View full text |Cite
|
Sign up to set email alerts
|

Risk of revision for infection in primary total hip and knee arthroplasty in patients with rheumatoid arthritis compared with osteoarthritis: A prospective, population‐based study on 108,786 hip and knee joint arthroplasties from the Norwegian Arthroplasty Register

Abstract: Objective. To compare differences in the risk of revision for infection and changes in risk over time and in time from primary surgery to revision for infection after total hip replacement (THR) and total knee replacement (TKR) in rheumatoid arthritis (RA) and osteoarthritis (OA) patients. Methods. In the Norwegian Arthroplasty Register, 6,629 and 102,157 primary total joint replacements in patients with RA and OA, respectively, were identified from 1987 (1994 for knees) until 2008. Survival analyses with revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
106
4
12

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(135 citation statements)
references
References 42 publications
11
106
4
12
Order By: Relevance
“…Similar to other studies that have examined revision risk factors, we identified sex, age, BMI, diagnosis, and diabetes as patient risk factors of revision [17,28,40,41]. Two studies [5,37] examined predictors for inclusion in total joint arthroplasty risk calculators.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to other studies that have examined revision risk factors, we identified sex, age, BMI, diagnosis, and diabetes as patient risk factors of revision [17,28,40,41]. Two studies [5,37] examined predictors for inclusion in total joint arthroplasty risk calculators.…”
Section: Discussionmentioning
confidence: 98%
“…In case of advanced stage large-joint OA, standard treatment consists in surgical removal of the affected joint and its replacement with an artificial joint. Total joint arthroplasty represents rather extensive surgery which is associated with considerable risk of serious side effects and post-operative complications including myocardial infarction, stroke, systemic infection or increased risk of death after TJA [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Although early stages of OA can be alleviated by physical therapy, weight loss, non-steroid analgesic drugs, and chondroprotectives, risk of death at 30 and 90 days after surgery, and the life-span of the prosthesis is limited [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…They found that MI THA was associated with a significantly increased risk of early revision compared with conventional THA (1.4 years versus 14.7 years, odds ratio = 26.5). Finally, Schrama et al [20] evaluated differences in the risk of revision THA for infection among patients with rheumatoid arthritis and osteoarthritis. Using data from the Norwegian Arthroplasty Register, they reported a higher risk of late ([ 6 years postoperatively) infection leading to revision THA in patients with rheumatoid arthritis compared to patients with osteoarthritis [20].…”
Section: Discussionmentioning
confidence: 99%